PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 011 PEMATANG INDAH KECAMATAN KELAYANG - Roma Yuni; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPA class fourth students of SDN 011 Pematang Indah Kecamatan Kelayang by implementing cooperative learning model NHT. Pelakasanaannya process is done in the form of stages or cycles consisting of planning, implementation, observation and reflection. Subjects of this study amount to 9 students consisting of three boys and six girls. Based on the results of the study the average value before implementation of cooperative learning model NHT is 61.11. In the first cycle UH 1 daily value increased to 66.67 students who have increased as much as 9.09%, with the number of students who completed 3 students (33.33%). In the second cycle increased learning outcomes as much as 29.09% to 78.89. All students completed the implementation of the UH 2 were 9 people (100%). The implementation of cooperative learning model NHT could improve the quality of learning that can be seen from the activities of teachers and students. The first meeting of the first cycle obtained a percentage of 75% with good criterion. At the second meeting to 83.33% with good criterion once. At the first meeting of the second cycle which is obtained by percentage of 87.5% with good criterion once. At the second meeting increased to 91.67% with good criterion once. In addition, in the first cycle of the first meeting of the learning ability of students to implement in accordance with the direction of teachers obtain success percentage of 62.5% with sufficient criteria. At the second meeting increased to 70.83% with good criterion. At the first meeting of the second cycle increased percentage of 87.5% with good criterion once. At the second meeting, increased to 95.83% with good criterion once. Thus, it can be concluded that the application of cooperative learning model NHT can improve learning outcomes IPA class fourth students of SDN 011 Pematang Indah Kecamatan Kelayang Keywords: NHT Model Cooperative Learning, Learning Outcomes IPA